Food consumption and cardiovascular risk factors in European children: the IDEFICS study. Issue 3 (6th December 2012) - Bel‐Serrat, S.; Mouratidou, T.; Börnhorst, C.; Peplies, J.; De Henauw, S.; Marild, S.; Molnár, D.; Siani, A.; Tornaritis, M.; Veidebaum, T.; Krogh, V.; Moreno, L. A.
Summary: What is already known about this subject: Few studies addressing the relationship between food consumption and cardiovascular disease or metabolic risk have been conducted in children. Previous findings have indicated greater metabolic risk in children with high intakes of solid hydrogenated fat and white bread, and low consumption of fruits, vegetables and dairy products. What this study adds: In a large multinational sample of 2 to 9 years old children, high consumption of sweetened beverages and low intake of nuts and seeds, sweets, breakfast cereals, jam and honey and chocolate and nut‐based spreads were directly associated with increased clustered cardiovascular disease risk. These findings add new evidence to the limited literature available in young populations on the role that diet may play on cardiovascular health. Objective: To investigate food consumption in relation to clustered cardiovascular disease (CVD) risk. Methods: Children ( n  = 5548, 51.6% boys) from eight European countries participated in the IDEFICS study baseline survey (2007–2008). Z ‐scores of individual CVD risk factors were summed to compute sex‐ and age‐specific (2–<6 years/6–9 years) clustered CVD risk scores A (all components, except cardiorespiratory fitness) and B (all components). The association of clustered CVD risk and tertiles of food group consumption was examined. Results: Odds ratio (OR) of having clustered CVD risk A increased in older children with higher consumption of chocolate and nut‐based spreads (boys: OR = 0.46; 95% CI = 0.32–0.69; girls: OR = 0.60; 95% CI = 0.42–0.86), jam and honey (girls: OR = 0.45; 95% CI = 0.26–0.78) and sweets (boys: OR = 0.69; 95% CI = 0.48–0.98). OR of being at risk significantly increased with the highest consumption of soft drinks (younger boys) and manufactured juices (older girls). Concerning CVD risk score B, older boys and girls in the highest tertile of consumption of breakfast cereals were 0.41 (95% CI = 0.21–0.79) and 0.45 (95% CI = 0.22–0.93) times, respectively, less likely to be at risk than those in tertile 1. Conclusions: High consumption of sugar‐sweetened beverages and low intake of breakfast cereals, jam and honey, sweets and chocolate and nut‐based spreads seem to adversely affect clustered CVD risk.